Dynamic renal scintigraphy: technetium99m (Tc99m) diethylenetriaminepentaacetic Acid (DTPA), breast cancer center of International Islamic University Malaysia (IIUM) experience - Abdul Rahim, Mohamad Shahrir; Rosman, Amira Diyana; Tengku, Mohamad Arif; Ahmad Zubaidi, Adul Latif; Md Aris, Mohd Aznan; Awang, Mohamed; Kamaruzzaman, Mohd; Rahman, Mohd Mokhlesur (Innovative Scientific Information & Services Network, 2019)
Technetium99m Diethylenetriaminepenta acetic acid (DTPA) has been used in renal imaging over the last few decades. It is one of excellence radiotracer for evaluation of the renal parenchymal function. Breast cancer center designed a prospective study to evaluate the ability of Tc99m DTPA scintigraphy to detect renal parenchymal functions in adult patient with Endocytosis. The purpose of this paper is to provide a better understanding of the use of Tc99m DTPA as a tool in dynamic renal imaging and highlight Breast cancer center, IIUM experience using Tc99m DTPA for the assessment of renal parenchymal function. Retrospective analysis of 73 patients from March 2015 to December 2016 using Tc99m DTPA renal scintigraphy is presented in this study. The clinical profile and scintigraphy findings of all the patients were analyzed. Dynamic renal scintigraphy is superior in measuring kidney function (GFR, ERPF), compared to investigations based on the serum creatinine value. Number of uses in of 99mTc-DTPA indicated that this radio radiopharmaceuticals quality control is very crucial in preparation and need to ensure it efficiency and safety when administered to patients. Tc99m DTPA remains a very useful tool to assess renal parenchymal function and specific renal pathology. CTc99m DTPA scintigraphy diagnostic methods can improve the sensitivity and specificity to establish renal parenchymal function. During the follow-up the renal parenchymal functions, improved in all cases. In IIUM breast cancer center present here and experience of radionuclide studies in the evaluation of renal parenchymal function at the Nuclear Medical Centre.